Penerapan Arsitektur Perilaku pada Sekolah Terpadu TK, Sekolah Dasar, Sekolah Menengah Pertama Dan Sekolah Menengah Atas di Kelapa Gading Jakarta Utara - ndruru, oozisokhi; Eni , Sri Pare; Erwin, Bambang (Universitas Medan Area, 2025)
This study aims to design an integrated school encompassing Kindergarten, Elementary School, Junior High School, and Senior High School levels in Kelapa Gading, North Jakarta, using a behavioral architecture approach. This approach focuses on optimizing the physical school environment to support positive behavior, social interaction, and more effective teaching and learning processes. The research methodology includes literature studies, field observations, and interviews with relevant stakeholders. The findings reveal that the current layouts of schools in the area are not well-integrated, hindering collaboration among students, teachers, and staff, and inadequately supporting learning activities. The design considers psychological and social factors that influence the learning process, emphasizing open, flexible, and adaptive spaces to facilitate social interaction, collaboration, and active learning. Key features include flexible classrooms, centralized communal areas, safe pedestrian pathways, and adequate access between school levels to ease student transitions. The implementation of this design is expected to create a more inclusive and interactive learning environment, ultimately enhancing student engagement, academic performance, and overall well-being. This research contributes to the development of educational architecture, particularly in designing behavior-based integrated school environments in urban areas.